Diagnostic accuracy of basal cell carcinoma in dermatology setting in Serbia: A single-center study - Ivkov-Simić Milana; Gajić Branislava; Ogorelica Dejan; Gajinov Zorica (Vojnosanitetski Pregled)
Background/Aim. The growing incidence of skin tumors requires an accurate diagnosis. Dermoscopy, especially in vivo, enhances the diagnosis of basal cell carcinoma (BCC). Total body skin examination (TBSE), a visual inspection of the patient’s total body surface, is considered a basic step in the dermatological exam, especially in skin cancer screening. However, TBSE is still a matter of debate regarding its expediency in a real clinical setting. The aim of this study was to analyze the diagnostic accuracy of BCC detected and treated by referred dermatologists. Methods. The retrospective analysis included a five-year period of BCC detection during TBSE by visual inspection and dermoscopy. We calculated sensitivity, specificity and positive predictive value for BCC using histopathological results as the correct diagnosis. Results. Out of 3,346 biopsied skin tumors, 49.58% were malignant and 50.42% benign. The most common malignant tumor was BCC, accounting for 84.09%. Localization of BCCs was mainly on the trunk (38.92%) and the H-zone of the face (37.63%). Other localizations were face (non-H-zone) (6.67%), neck (3.01%), scalp (3.37%), arms (6.88%) and limbs (3.51%). Of all BCCs, 0.83% were recurrent BCC. The sensitivity for the diagnosis of BCC was 97.71%, and the positive predictive value was 95.08%. Conclusion. In the dermatology setting, TBSE and visual inspection with in vivo dermoscopy result in a very good diagnostic performance of BCC.